Candidate T cell epitopes of the human La/SSB autoantigen. - Davies, M; Taylor, E; Gordon, C; Young, S; Welsh, K; Bunce, M; Wordsworth, B; Davidson, B; Bowman, S (2002)
OBJECTIVE: To identify T cell epitopes of the human La autoantigen involved in the generation of anti-Ro/La autoantibodies. METHODS: Molecular techniques were used for HLA typing of 219 white patients with systemic lupus erythematosus and 125 white patients with primary Sjögren's syndrome. Anti-Ro/La antibody levels were measured by enzyme-linked immunosorbent assay. Peripheral blood mononuclear cell responses to an overlapping series of synthetic 15-mer peptides spanning the entire La sequence were examined in pools or individually in conventional 7-day proliferation assays. RESULTS: HLA typing confirmed that the HLA-DR3/DQ2 haplotype is closely associated with the occurrence of anti-Ro/La antibodies, and that the frequency of HLA-DR1 and DR4 haplotypes is reduced among antibody-positive patients. We identified 3 regions of the La sequence likely to contain T cell epitopes and 1 peptide, La 49-63, that generated a low-level but clear-cut T cell proliferative response. The HLA restrictions of these responses mirrored the HLA association data from the cohort study. Among individuals who were HLA-DR3 positive, there was no difference between patients and controls in the proliferative response to the La 49-63 peptide. CONCLUSION: Our data suggest that these are naive T cell responses, and that the identification of T cell epitopes involved in the generation of anti-Ro/La autoantibodies should focus on alternative candidate antigens.